Initiating home spirometry for children during the COVID-19 pandemic – A practical guide. (June 2022) - Richardson, C.H.; Orr, N.J.; Ollosson, S.L.; Irving, S.J.; Balfour-Lynn, I.M.; Carr, S.B.
Abstract: The COVID-19 pandemic has led to a rapid escalation in use of home monitoring and video consultations in children with a variety of chronic respiratory conditions. Our department set up a home spirometry service from scratch once it became evident that we needed to keep patients away from hospital clinics whenever possible. We faced a number of challenges but now have around 400 children using home spirometers. There are a number of portable spirometers available, some with online platforms. The technology, particularly the software/apps interface, has been improved by the companies in response to issues that have arisen. We believe the use of home monitoring is here to stay.